VALIDATED SPECTROPHOTOMETRIC METHODS FOR SIMULTANEOUS ANALYSIS OF PYRIMETHAMINE AND SULPHADOXINE IN PHARMACEUTICAL DOSAGE FORMS - Meena, S.; Sandhya, S. M. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT Objective: Two simple, accurate and reproducible spectrophotometric methods have been developed and validated for simultaneous estimation of pyrimethamine and sulphadoxine in combined dosage form. Methods: Pyrimethamine shows maximum absorbance at 285.6 nm and sulphadoxine shows maximum absorbance at 273.4 nm. In dual wavelength method, two wavelengths were selected for each drug in a way so that the difference in absorbance is zero for another drug. Pyrimethamine shows equal absorbance at 278 and 295 nm, where the difference in absorbance was measured for determination of sulphadoxine. Similarly, difference in absorbance at 246 and 298 nm were measured for determination of pyrimethamine. For multicomponent mode method; the sampling wavelengths selected were 285.6 and 273.4 nm. Results: Linearity for detector response was observed in the concentration range of 3-18 Âµg/mL for pyrimethamine and 7-42 Âµg/mL for sulphadoxine for method I, 5-30 Âµg/mL for pyrimethamine and 10-60 Âµg/mL for sulphadoxine for method II respectively. Accuracy and precision studies were carried out and results were satisfactory. The proposed methods were validated as per ICH guidelines. Conclusion: The developed methods are simple, precise, rugged and economical. The utility of the methods has been demonstrated by analysis of commercially available formulations. Â Key words: Pyrimethamine, Sulphadoxine, Dual wavelength method, Multicomponent analysis, Method validation.